Critical stylistics of online news representation of the 2017 Gulf Crisis on Al Arabiya and Al Jazeera - Jasim, Alkhafaji Samir Abdulhasan (2024)
The 2017 Gulf Crisis, where Saudi Arabiya and its allies severed all diplomatic ties and imposed a complete blockade on Qatar. Media has also played the greatest role in flaming the crisis and mobilizing public perception. Despite the significance of media to frame the discourse of international conflicts, no attention has been given to the way certain stylistic strategies are used by Al Arabiya and Al Jazeera in the coverage of the Gulf Crisis. The lack of research leaves a gap in the way to a full understanding of how language elaborates narratives and encodes ideological positions in the regional media landscaped. This study investigates how the 2017 Gulf Crisis was represented in online news articles by Al Arabiya and Al Jazeera, focusing on the linguistic strategies used to encode ideologies. The objectives are to identify the stylistic strategies used by Al Arabiya and Al Jazeera in representing the Gulf Crisis 2017 and to discuss their ideological implications. The study uses a qualitative approach, analyzing news articles from both platforms’ English versions, to uncover embedded ideologies and stylistic strategies. The analysis shows that various strategies both media adopt to coincide with their geopolitical positionings. Al Arabiya narrative often uses charged words, ambiguous quantifiers, nominalizations, and noun phrases casting Qatar in negative light for alleged terrorism support and for causing regional turmoil. Transitivity used to present Saudi-led bloc as proactive actors fighting against extremism, while Qatar was portrayed passively receiving action and accusation. Equating and contrasting were used in the creation of a binary opposition between the “righteous” Saudi-led bloc and the “destabilizing” forces associated with Qatar. Exemplifying and enumerating used to count the purported transgressions of Qatar, augmenting the perceived threat. By contrast, Al Jazeera framed Qatar as a victim of unjust aggression by using emotional language, precise quantification, and metaphors and complex noun phrases to humanize the impact of the blockade. Transitivity choices showed Qatar as being targeted in an unfair way, while equating and contrasting showed extreme severity of the blockade. Exemplifying and enumeration were used to describe socio-economic and human rights impacts on people. The ideological implications run deeper, Al Arabiya’s strategies align with an ideology that legitimizes Saudi-led bloc actions and portrays Qatar as a destabilizing force, promoting Saudi hegemony. Al Jazeera’s strategies support Qatar’s sovereignty, critique regional hegemony, and highlight human rights violations. Both outlets have strategically framed public perception, influencing readers’ understanding of legitimacy, moral positioning, threat construction, regional power dynamics, and terrorism discourse. The study concludes that both platforms strategically used linguistic strategies to create ideologically loaded narratives, legitimizing their geopolitical position while making the others illegitimate. Future research should examine this framing across different media formats or conducting longitudinal analyses to better understand the changing geopolitical dynamics.